The Analysis of Phosphorus and Potassium As Macronutrients And Zinc As A Micronutrient In Solid Organic Fertilizer Derived From Biowaste As An Applied Science Innovation Supporting SDG 2, 9, And 12 - David, Daviella; Sari, Meidita Kemala; Siregar, Sri Hilma (Urecol Journal. Part D: Applied Sciences, 2025)
Sustainable agriculture plays a crucial role in achieving SDG 2 (Zero Hunger), SDG 9 (Industry, Innovation and Infrastructure), and SDG 12 (Responsible Consumption and Production). One strategic approach to achieving these goals is the utilization of solid organic fertilizers derived from biowaste, which can enhance soil fertility and strengthen food security. The effectiveness of such fertilizers is highly influenced by their macro- and micronutrient content, which must comply with national quality standards. This study analyzes the levels of phosphorus (P), potassium (K), and zinc (Zn) in three samples of solid organic fertilizer (PAP 01, PAP 02, and PAP 03) based on the Indonesian National Standard (SNI) 7763:2018, along with moisture content as an indicator of product stability. Phosphorus was analyzed using UV-Vis spectrophotometry, while potassium and zinc were measured using Atomic Absorption Spectrophotometry (AAS). The results showed moisture content ranging from 5.02% to 45.24%, P?O? from 1.47% to 4.00%, K?O from 1.58% to 2.86%, and Zn at 261.22 mg/kg, with good analytical precision (RPD and RSD < 5%). These findings indicate that solid organic fertilizers meet the minimum nutrient requirements for plant growth. The application of analytical chemistry in this study not only ensures product quality but also supports applied science innovation in promoting sustainable agriculture and community empowerment through science-based development.